The Influence of Compensation and Career Development on Employee Performance at PT. Pho 24 Indonesia, South Jakarta - Nariah, Nariah; Mona, Zefnat S (Jurnal Multidisiplin Sahombu, 2025)
This This study investigates the influence of compensation and career development on employee performance at PT. Pho 24 Indonesia, South Jakarta. Utilizing a quantitative approach with a saturated sampling technique, data were collected from all 90 employees through structured questionnaires. The results indicate that both compensation and career development have a significant and positive effect on employee performance, both partially and simultaneously. Regression analysis shows that fair compensation and clear career development pathways contribute to increased motivation, job satisfaction, and employee engagement. Furthermore, the findings highlight that inadequate compensation and limited promotion opportunities have negatively impacted performance levels over time. Classical assumption tests confirm that the regression model meets the requirements of normality, multicollinearity, and heteroscedasticity. The study emphasizes the need for strategic human resource practices to enhance employee output. It is recommended that the company periodically reviews its compensation schemes and implements structured career development programs to support organizational success.